Assessing the African Union's 2016–19 Human Rights Action Planning Process: Embracing, and De-Coupling from, the Conventional "Ideal". (June 2020) - Okafor, Obiora; Miyawa, Maxwel; Bawa, Sylvia; Odumosu-Ayanu, Ibironke
Abstract: This article assesses the African Union's planning process regarding the development of the African Human Rights Action Plan (AHRAP) against the dominant or conventional "ideal" or model of human rights action planning. It examines the extent to which the AU's process followed or departed from the conventional model, the strengths and weaknesses of the AU human rights action planning process, and the lessons scholars and policymakers have learned about more effective and more locally responsive human rights action planning. In doing so, the article sequentially addresses the following specific themes: human rights action planning as a concept and its essential elements; the key characteristics and features of the conventional "ideal" human rights action planning process; and the extent to which the AU plan conformed to or departed from this conventional process, and its import. It also teases out some key insights and lessons learnt (in terms of strengths and weaknesses) in respect of the AHRAP planning process.